2022
DOI: 10.1159/000526595
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacist Intervention Reduces Potentially Inappropriate Prescriptions in a Geriatric Perioperative Care Unit Dedicated to Hip Fracture

Abstract: <b><i>Introduction:</i></b> Clinical pharmacist (CP) intervention improves drug prescription by identifying potentially inappropriate prescriptions (PIPs). Geriatric perioperative care units (UPOGs) provide enhanced care for patients with hip fracture, including drug prescription. However, it is not known whether adding a CP intervention in a UPOG decreases the number of PIPs. This study aimed to evaluate the effect of a CP intervention, combining an implicit and an explicit method, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Previous studies have described prevalent use of PIMs in hip fracture patients, such as falls-risk increasing drugs [ 23 , 64 ]. Our results are comparable to previously described clinical pharmacist initiatives, which have reduced PIMs in older inpatients [ 65 ], outpatient clinics [ 66 ], and hip fracture patients [ 35 ]. Through less PIMs and a higher proportion receiving osteoporosis therapy, the intervention patients may have experienced fewer fractures and a lower mortality if observed for a longer period than in this study, e.g.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have described prevalent use of PIMs in hip fracture patients, such as falls-risk increasing drugs [ 23 , 64 ]. Our results are comparable to previously described clinical pharmacist initiatives, which have reduced PIMs in older inpatients [ 65 ], outpatient clinics [ 66 ], and hip fracture patients [ 35 ]. Through less PIMs and a higher proportion receiving osteoporosis therapy, the intervention patients may have experienced fewer fractures and a lower mortality if observed for a longer period than in this study, e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have included clinical pharmacists in discharge management and care transitions, which resulted in optimised medication information and reduced discrepancies [11,[29][30][31][32]. Through the medication reviews, clinical pharmacists have contributed to optimised pharmacotherapy by reducing the number of PIMs, suggested to start recommended therapies, and increasing medication appropriateness [33][34][35]. Furthermore, clinical pharmacist interventions have also shown to reduce readmissions and mortality [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, previous reports have shown that including pharmacists in multidisciplinary geriatric teams provides more benefits than isolated pharmacists’ interventions [ 20 ]. Moreover, a recent report has demonstrated that the intervention of a clinical pharmacist can improve medical prescriptions by diminishing the total PIDP incidence in a cohort of older patients admitted for acute hip fracture [ 36 ]. In a small intervention cohort of 59 patients, Leguillon et al obtained a reduction around 65% of total PIDP between admission and discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In a small intervention cohort of 59 patients, Leguillon et al obtained a reduction around 65% of total PIDP between admission and discharge. This effect clearly improves the comparison of the control group that, without the involvement of a clinical pharmacist, achieves a very slight prescription adequacy in terms of PIDP incidence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight the positive impact of clinical pharmacists in mitigating medication omissions, addressing incompleteness in treatment plans and reducing the risk of adverse events associated with patient therapy. Incorporating clinical pharmacists into surgical teams can lead to improved medication management and enhanced patient safety during the perioperative period [3,[6][7][8]. A 2.7-fold increase in the risk of experiencing postoperative complications has been revealed in surgical patients treated with preadmission medications compared to those not taking preadmission medications [9].…”
Section: Introductionmentioning
confidence: 99%